A comparison of heritable abnormal lipoprotein patterns as defined by two different techniques - Fredrickson, D. S. (1968)
Eight plasma lipoprotein patterns currently employed in attempts to identify different forms of familial dyslipoproteinemia have been compared by two methods. The first (NIH method) is based on paper electrophoretic patterns produced by the four lipoprotein classes obtained by paper electrophoresis in albuminated buffer, coupled with the measurement of the total cholesterol of three of these lipoprotein classes and ascertainment of abnormal flotation of beta-migrating lipoproteins. The second (Donner method) is based on lipoprotein patterns obtained in the analytical ultracentrifuge, adapted for computer analysis and complemented by chemical determination of the concentration of chylomicrons (lipoproteins of S(f)° > 400). Pooled samples representing patients with five types of familial hyperlipoproteinemia and three different forms of inherited lipoprotein dificiency were separately analyzed. For six of the eight pools, both methods provided a distinctive lipoprotein pattern in terms of changes in one or more variables. For the remaining two pools, type IV hyperlipoproteinemia and the heterozygote for Tangier disease, both methods provided identical but not unique patterns. The results indicate that lipoprotein analyses obtained by either method may be used interconvertibly in further genetic and other clinical studies.